Three‐year effectiveness and safety of vedolizumab therapy for inflammatory bowel disease: a prospective multi‐centre cohort study. Issue 1 (5th June 2019) - Amiot, Aurelien; Serrero, Melanie; Peyrin‐Biroulet, Laurent; Filippi, Jerome; Pariente, Benjamin; Roblin, Xavier; Buisson, Anthony; Stefanescu, Carmen; Trang‐Poisson, Caroline; Altwegg, Romain; Marteau, Philippe; Vaysse, Thibaud; et al.
Summary: Background: Cohort studies have described the short‐term effectiveness and safety of vedolizumab in treating patients with Crohn's disease (CD) and ulcerative colitis (UC), but data beyond 1 year are lacking. Aim: To assess the effectiveness and safety of vedolizumab after 162 weeks in patients with UC and CD. Methods: Between June and December 2014, 294 patients including 173 patients with CD and 121 with UC were treated with vedolizumab induction therapy. Among them, 149 continued to be treated with vedolizumab beyond week 54 (78 patients with CD and 71 with UC). Disease activity was assessed using the Harvey‐Bradshaw Index for CD and the partial Mayo Clinic score for UC. The primary outcome was steroid‐free clinical remission at week 162, computed for the whole population included at week 0. Results: Steroid‐free clinical remission rates at week 162 were 19.9% and 36.1% in patients with CD and UC respectively. Vedolizumab dose optimisation to 300 mg every 4 weeks instead of 300 mg every 8 weeks was at investigator's discretion and occurred in 58.7% and 52.1% of patients with CD and UC respectively. The 1‐, 2‐ and 3‐year persistence rates of vedolizumab were 48.5%, 31.4% and 26.3% respectively, in patients with CD and 61.0%, 49.9% and 42.9% respectively, in patients with UC. No new safety signal was identified. Conclusion: Vedolizumab is able to maintain steroid‐free clinical remission in patients with UC and CD up to week 162. Loss of response resulting in discontinuation of vedolizumab occurred in 10% of patients per year.